KELEMBAGAAN URUSAN PANGAN DARI MASA KE MASA DAN KEBIJAKAN KETAHANAN PANGAN - Saragih, Juli Panglima (Jurnal Ekonomi & Studi Pembangunan, 2016)
Since independence of Indonesia, authorities and functions of national agency for food affairs often changed until nowadays. This phenomenon can impact on acchieving national food safety. In Presiden Suharto era, agency for food affairs—namely Bulog was successful in stabilizing food price although its statuta as non-profit institution. Meanwhile, politic of food-stock supply in 1998 also more or less give impact on achieving it. Both Law Number 7 Year of 1996 and Law Number 12 Year of 2012 do not clearly regulate about institution on food affairs. Since Bulog became a business company in 2003, Bulog was failure in stabilizing some food prices, except rice. As qualitatif research, this study uses descriptive-analysis as tool to solve problem by analysing historical data relevant with the topic. This study explain that eventhough government has already set up Bulog as single agency for food affairs, but food problems rise up due to multi-dimension problems and complexity of government policies. In this concern, it is needed policy coordination amongst different govt institutions to overcome the increase of food prices. Problems of distribution and marketing also impact on achievement of food safety.